2013
DOI: 10.1016/j.yhbeh.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol administration blocks stress-induced impairments in memory and anxiety, and alters hippocampal neurotransmitter receptor expression in male rats

Abstract: Chronic exposure to stress has many deleterious effects on behavior, which can often lead to self-medication with anxiolytics, antidepressants, or alcohol. We determined the effects of alcohol administration following a stressor on established behavioral, physiological, and neural responses to stress. Male Sprague-Dawley rats received: No alcohol / No stress (CON), Alcohol alone (ALC), Stress alone (STR), or Stress plus Alcohol (STR+ALC). For seven consecutive days, two cohorts received an oral dose of 2 g/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 64 publications
(78 reference statements)
2
29
1
Order By: Relevance
“…In the present study, chronic intake resulted in increases in depression, and the effects were often greater in females than in males [30]. Another study found that chronic alcohol increased depressive-like behaviours in females,which was an effect not observed in males [31]. Consistent with the experimental results, alcohol treatment increased immobility, a sign of depressive-like behaviour, in the GX-eth rats.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, chronic intake resulted in increases in depression, and the effects were often greater in females than in males [30]. Another study found that chronic alcohol increased depressive-like behaviours in females,which was an effect not observed in males [31]. Consistent with the experimental results, alcohol treatment increased immobility, a sign of depressive-like behaviour, in the GX-eth rats.…”
Section: Discussionsupporting
confidence: 89%
“…For object placement, one week of restraint stress did not affect memory in males while 3 weeks impaired memory (Beck and Luine, 2002; Gomez et al, 2012). In object recognition, either one or three weeks of stress impaired male memory (Beck and Luine, 1999; 2002; Gomez et al, 2013). Overall, the time course of stress effects on male cognition is consistent with the conclusions of Selye (1976) and others who showed that short-term stress elicits adaptive physiological responses but that continued stress exposure results in maladaptive responses.…”
Section: Sex Differences and Allostatic Loadmentioning
confidence: 99%
“…In tests assessing spatial memory (not learning), chronic stress also generally impairs male performance (See Conrad, 2010 for review). Spatial memory in both the object placement (Beck and Luine, 1999; Bowman et al, 2009; Gomez et al, 2012; Beck and Luine, 2002) and the Y-maze task is impaired following 3 weeks of daily restraint (Conrad et al, 2003; Wright and Conrad, 2005; Gomez et al, 2013). As shown for the object placement task (left two bars of Fig.…”
Section: Chronic Stress Elicits Sexually Differentiated Effects Onmentioning
confidence: 99%
“…Stressed male rats and mice are unable to significantly discriminate between known and new objects in the NOR test [41, 42] or on a test of temporal order recognition memory (TORM) [43 and Figure 5A]. Spatial memory in males is also impaired by chronic stress in NOP (Figure 4B) [41, 44, 45] and the Y-maze [46, 47, 48]. Thus, chronic stress impairs learning and memory in male rodents in a variety of tasks.…”
Section: Function(s) Of Rapid Estrogen Induced Changes In Memorymentioning
confidence: 99%